Biotinylated-lipid bilayer coated mesoporous silica nanoparticles for improving the bioavailability and anti-leukaemia activity of Tanshinone IIA. (31st October 2018) - Li, Zhe; Zhang, Yongtai; Zhang, Kai; Wu, Zimei; Feng, Nianping
Abstract: The oral bioavailability and anti-leukaemia activity of Tanshinone IIA (TanIIA) were enhanced by using biotinylated-lipid bilayer coated mesoporous silica nanoparticles (Bio-LB-MSNs) as a vehicle. The in vitro release of TanIIA from TanIIA@MSNs was significantly higher than that of the TanIIA powder ( p  < .05). The in vitro cellular uptake of TanIIA by Caco-2 was increased by loading drug into the Bio-LB-MSNs more than those of the compared nanovehicles without biotin modification. The apparent in situ permeability coefficient ( P app ) of TanIIA@Bio-LB-MSNs showed nearly 2.5-, 1.6- and 1.3-fold improvement compared with the TanIIA powder, TanIIA@MSNs and TanIIA@LB-MSNs. Following oral administration of TanIIA@Bio-LB-MSNs in rats, the area under the plasma concentration–time curves ( AUC ) of TanIIA was 3.4-, 1.9- and 2.4-fold larger than those in the groups received a pure TanIIA powder, TanIIA@MSNs or TanIIA@LB-MSNs, indicating that drug bioavailability was enhanced by using MSNs as a vehicle, and further improved significantly through biotin modification. The in vitro anti-leukaemia activity of TanIIA was also enhanced after being loaded into nanoparticles and modification, with 50% inhibitive concentration (IC50 ) of NB4 cells at 6.5 μM for TanIIA@Bio-LB-MSN. In conclusion, Bio-LB-MSNs are a promising vehicle to improve the oral bioavailability and anti-leukaemia activity of the poorly water-soluble drug TanIIA.